2014
DOI: 10.1002/asi.23189
|View full text |Cite
|
Sign up to set email alerts
|

Using content and network analysis to understand the social support exchange patterns and user behaviors of an online smoking cessation intervention program

Abstract: Informational support and nurturant support are two basic types of social support offered in online health communities. This study identifies types of social support in the QuitStop forum and brings insights to exchange patterns of social support and user behaviors with content analysis and social network analysis. Motivated by user information behavior, this study defines two patterns to describe social support exchange: initiated support exchange and invited support exchange. It is found that users with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
1
49
0
1
Order By: Relevance
“…Two of them utilised the focus group methods, and one of them involved the interview method . The other eight research collected data directly from the social media platforms . Several (eight of 21) studies focused on the users at specific locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them utilised the focus group methods, and one of them involved the interview method . The other eight research collected data directly from the social media platforms . Several (eight of 21) studies focused on the users at specific locations.…”
Section: Resultsmentioning
confidence: 99%
“…29 The other eight research collected data directly from the social media platforms. [30][31][32][33][34][35][36][37] Several (eight of 21) studies focused on the users at specific locations. For example, Benetoli et al 29 described the user behaviour of Australian consumers on Facebook while Kishimoto and Fukushima 26 reported the Japanese consumers' use of social media for drug information.…”
Section: Study Selectionmentioning
confidence: 99%
“…(Cobb, ; Hajli, ; Zhang & Yang, ). Studies have shown social support to be a product of social connections (Chuang & Yang, ; Lin, Hsu, Cheng, & Chiu, ; Zhang & Yang, ) and a predictor of health outcomes, such as greater well‐being (Bui, Yen, & Honavar, ; Wright, ). Rubenstein () showed information and emotional support was exchanged among members of an online breast cancer group.…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…For example, a self-initiated post often includes a description of the problem for which support is being sought. Replies to an original post from other online users can indicate attention, engagement, and responsiveness to the post (Himelboim, 2008;Huffaker, 2010;Zhang & Yang, 2015). Seen in this light, social networks based on reply relationships offer a fruitful venue for studying the interactive and reciprocal nature of communication in online support forums.…”
Section: Online Support Forums As Networkmentioning
confidence: 99%